Pengaruh functionality dan usability terhadap value for time dan value for money pengguna aplikasi Airbnb Surabaya - Oliandes Sondakh; Hananiel Mennoverdi Gunawan; Renna Magdalena (Jurnal Inspirasi Bisnis dan Manajemen, 2023)
Abstract. This study aims to examine the effect of Functionality and Usability on Value for Time and Value for Money. The research design uses a quantitative approach with a questionnaire as a data collection instrument. Data was collected from 100 respondents from a population of travelers who had used the Airbnb application at least 2 times in different periods in the last 3 years with a minimum booking time of 3 days per period. Hypothesis testing was carried out using the multiple linear regression method. The results of hypothesis testing show that Functionality has a significant effect on Value for Time and Value for Money; while Usability was found to have no significant effect on Value for Time and Value for Money. Thus, Airbnb is expected to be able to focus on providing more useful information to customers. Keywords: Functionality; Usability; Value for Time; Value for Money. Abstrak. Penelitian ini bertujuan untuk menguji pengaruh dari Functionality dan Usability terhadap Value for Time dan Value for Money. Desain penelitian menggunakan pendekatan kuantitatif dengan kuisioner sebagai instrument pengambilan data. Data dikumpulkan dari 100 orang responden dari populasi para pelancong yang telah menggunakan aplikasi Airbnb minimal 2 x pada periode yang berbeda dalam 3 tahun terakhir dengan lama waktu pemesanan minimal 3 hari per periodenya,  Pengujian hipotesis dilakukan dengan menggunakan metode regresi linear berganda. Hasil pengujian hipotesis menunjukkan bahwa Functionality berpengaruh signifikan terhadap Value for Time dan Value for Money; sementara Usability ditemukan tidak berpengaruh signifikan terhadap Value for Time dan Value for Money. Dengan demikian, Airbnb diharapkan mampu berfokus pada penyediaan informasi yang lebih bermanfaat kepada customer. Katakunci: Functionality; Usability; Value for Time; Value for Money